Comprehensive Genome Analysis of 6,000 USA SARS-CoV-2 Isolates Reveals Haplotype Signatures and Localized Transmission Patterns by State and by Country - Shen, Lishuang; Dien Bard, Jennifer; Biegel, Jaclyn A.; Judkins, Alexander R.; Gai, Xiaowu (Frontiers in Microbiology, 2020)
Genomic analysis of SARS-CoV-2 sequences is crucial in determining the effectiveness of prudent safer at home measures in the United States (US). By haplotype analysis of 6,356 US isolates, we identified a pattern of strongly localized outbreaks at the city-, state-, and country-levels, and temporal transmissions. This points to the effectiveness of existing travel restriction policies and public health measures in reducing the transmission of SARS-CoV-2.